(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to prepare training units using the isokine method by electrical stimulation suitable for the research sample and to identify the effect of using the isokine method by electrical stimulation on the peak and time of the electrical signal of the brachial muscle in the players of the School of Sports Talent, and to identify the effect of using the isokine method by electrical stimulation in the ejaculation of the players of the School of Talent. sports